Multiferroic behavior of the functionalized surface of a flexible substrate by deposition of Bi2O3 and Fe2O3 - Ramazanov, Shikhgasan; Sobola, Dinara; Ţălu, Ştefan; Orudzev, Farid; Arman, Ali; Kaspar, Pavel; Dallaev, Rashid; Ramazanov, Guseyn (Microscopy research and technique, 2022)
Thin films of bismuth and iron oxides were obtained by atomic layer deposition (ALD) on the surface of a flexible substrate poly(4,4′‐oxydiphenylene‐pyromellitimide) (Kapton) at a temperature of 250°C. The layer thickness was 50 nm. The samples were examined by secondary‐ion mass spectrometry, and uniform distribution of elements in the film layer was observed. Surface morphology, electrical polarization, and mechanical properties were investigated by atomic force microscope, piezoelectric force microscopy, and force modulation microscopy. The values of current in the near‐surface layer varied in the range of ±80 pA when a potential of 5 V was applied. Chemical analysis was performed by X‐ray photoelectron spectroscopy, where the formation of Bi2O3 and Fe2O3 phases, as well as intermediate phases in the Bi–Fe–O system, was observed. Magnetic measurements were carried out by a vibrating sample magnetometer that showed a ferromagnetic response. The low‐temperature method of functionalization of the Kapton surface with bismuth and iron oxides will make it possible to adapt the Bi–Fe–O system to flexible electronics. Layers of Bi2O3 and Fe2O3 of uniform thickness throughout the sample preparation by atomic‐layer deposition. The material forms a low‐temperature growth of the Bi–Fe–O phase on flexible substrates. Functionalization of the Kapton surface with ultrathin oxide layers. Kapton surface with oxides of bismuth and iron metals exhibits multiferroic properties.